2013
DOI: 10.1159/000350338
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Eosinophils by Bacteria Associated with Asthma

Abstract: Background: It has been suggested that there is a complex interaction between microbiota and various human diseases. Some bacteria have been reported to be involved in the inception and progression of asthma, and others in the protection against asthma. We know very little about the mechanisms by which bacteria do harm or good with regard to asthma. This study investigated whether bacteria exert differential effects on the functions of eosinophils, major effector cells in airway inflammation in asthma. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…The cytokine/chemokine response pattern observed in this study was not related to the microbial infection type (viral, bacterial or mixed); however, bacterial infection had lower cytokine/chemokine inducer effect. We have no clear explanation for this finding; however, it has been reported that bacteria exert differential effects on eosinophils (important cell in respiratory pathology), resulting in the exacerbation or the inhibition of inflammation in lung infection . As patients with ARI were infected by different bacteria, the serum values observed in bacterial infected patients could represent the result of those responses.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine/chemokine response pattern observed in this study was not related to the microbial infection type (viral, bacterial or mixed); however, bacterial infection had lower cytokine/chemokine inducer effect. We have no clear explanation for this finding; however, it has been reported that bacteria exert differential effects on eosinophils (important cell in respiratory pathology), resulting in the exacerbation or the inhibition of inflammation in lung infection . As patients with ARI were infected by different bacteria, the serum values observed in bacterial infected patients could represent the result of those responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hosoki and colleagues [ 66 ] reported that eosinophils responded with prominent release of EDN when challenged with pathogenic bacteria, such as Clostridium difficile , in contrast to a probiotic strain, such as Bifidobacteria , which did not induce EDN release. In a subsequent study, eosinophils again released EDN selectively, notably in response to provocation with Staphylococcus aureus , but not Hemophilus or Prevotella species [ 67 ]. The way in which eosinophils differentiate between distinct bacterial strains remains to be elucidated.…”
Section: Eosinophils Interact With Bacteria and Release Ednmentioning
confidence: 99%
“…Для большинства микроорганизмов этого рода характерна противовоспа-лительная активность в случае БА, которая заключается, в частности, в индукции синтеза интерлейкина 10 Т клет-ками [12]. Однако при тяжелой БА на фоне снижения общей представленности рода Prevotella отмечается более выраженное присутствие вида P. nanceiensis.…”
Section: обсуждение основного результата исследованияunclassified